Menelaah Makna Pernyataan Pejabat Publik Masa Kampanye Perspektif Picture Theory Ludwig Wittgenstein - Sofwan Jamil (Gunung Djati Conference Series, 2023)
This study aims to discuss one of the theories in the analytic philosophy tradition. In this study, Wittgenstein's concept of Picture Theory plays a role in examining the statements of public officials during the campaign period. This study uses a qualitative method with a descriptive-analytical approach. The analytical knife used in this study is Ludwig Wittgenstein's Picture Theory, while the objects studied are statements from public officials during the campaign period. The results and discussion of this study reveal that Wittgenstein played a central role in the development of philosophy, especially the realm of analytic philosophy. His first book, Tractatus Logico-Philosophicus, succeeded in bringing him success in the analytic philosophy tradition. In his first book, he produced a concept called Picture Theory. The meaning of language is obtained from its representation of the reality of the world. This theory is then used in this study to examine the meaning of statements made by public officials during the campaign period. The conclusion of this study is that there are statements from public officials that are said to be meaningless and meaningful. Because there are several statements that touch on metaphysical issues and in picture theory these things are meaningless.